Acute motor axonal neuropathy after ipilimumab and nivolumab treatment in melanoma brain metastases: A case report and review of the literature. (August 2021) - Piña, Yolanda; Evernden, Brittany R.; Khushalani, Nikhil; Margolin, Kim; Tawbi, Hussein; Tran, Nam D.; Macaulay, Robert; Forsyth, Peter; Peguero, Edwin
The use of immune checkpoint inhibitors including ipilimumab and nivolumab has expanded for several tumors including melanoma brain metastasis. These have resulted in a growing spectrum of neurologic immune-related adverse events, including ones that are rare and difficult to diagnose and treat. Here, we present a patient with melanoma brain metastasis who was treated with immune checkpoint inhibitors and developed an Acute Motor Axonal Neuropathy. To our knowledge, this is the first case of Acute Motor Axonal Neuropathy as an immune-related adverse event associated with combination treatment of ipilimumab and nivolumab, who was successfully treated. A 28-year-old woman with metastatic BRAF V600E melanoma developed melanoma brain metastasis and was enrolled on Checkmate 204, a Phase 2 clinical trial using ipilimumab (3 mg/kg intravenous) and nivolumab (1 mg/kg intravenous) every 3 weeks for four cycles, followed by monotherapy with nivolumab (240 mg intravenous) every 2 weeks. A few days after Cycle 2 of ipilimumab and nivolumab, she developed a pure motor axonal neuropathy consistent with Acute Motor Axonal Neuropathy. She was treated with several immunosuppressive treatments including high dose methylprednisolone, immune globulin, and infliximab, and her motor neuropathy eventually improved several months after onset of symptoms. Unfortunately, she had progression of her systemic disease and died several months later. This is the first case reported of Acute Motor Axonal Neuropathy associated with ipilimumab and nivolumab, successfully treated with immune-suppressive therapy. As the field of immunotherapy expands with the increasing use of the immune checkpoint inhibitors, it is critical to increase our knowledge and understanding of the neurologic immune-related adverse events associated with immune checkpoint inhibitors. This includes the spectrum of rare neurologic immune-related adverse events, which can be quite difficult to recognize and treat. Early consultations with neurology may expedite a diagnosis and treatment plan in patients with unexplained weakness receiving immune checkpoint inhibitor therapy.